Efektivas Shalat Tahajud terhadap Kesehatan Mental dan Tingkat Stres pada Remaja Indonesia: Systematic Literatur Riview - Eni Masruroh (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Mental health is an important aspect of adolescent life because it is closely related to emotional regulation, stress management, and social functioning. Adolescents in Indonesia are vulnerable to psychological problems caused by academic pressure, social demands, and emotional changes. One of the spiritual approaches believed to help improve mental health and reduce stress is tahajud prayer. This study aimed to analyze the effectiveness of tahajud prayer on mental health and stress levels among Indonesian adolescents using the Systematic Literature Review (SLR) method. The study employed the PRISMA model through the stages of identification, screening, eligibility, and inclusion. Article searches were conducted through Google Scholar and Garuda Journal databases using the keywords “tahajud prayer,” “mental health,” “stress,” and “Indonesian adolescents” within the publication range of 2021–2026. A total of 299 articles were identified, and after the selection process, 12 relevant articles met the inclusion criteria. The findings indicate that tahajud prayer has a positive effect on adolescents’ mental health by reducing stress, anxiety, and emotional pressure, while also improving emotional control, self-discipline, coping stress, and psychological well-being. The consistency and intensity of tahajud prayer were found to be associated with lower stress levels among adolescents and university students. Therefore, tahajud prayer can be considered an Islamic spiritual intervention that contributes positively to maintaining mental health and reducing stress among Indonesian adolescents.